2017
DOI: 10.1080/13813455.2017.1420665
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline ameliorates hyperthyroid condition in mice under cold stress

Abstract: Betel nut of Areca catechu is chewed by millions of people for increased capacity to work and stress reduction, but it contains arecoline that causes hypothyroidism. The aim is to investigate the role of arecoline on thyroid activity in cold stress in mice. Arecoline treatment (10 mg/kg body wt/day, for 7 d) caused a reduction in thyroid weight and ultrastructural degeneration of thyro-follicular cells with depletion of T and T levels compared with the control mice. Cold stress (4 °C for 2 h, twice daily, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The BP changes induced by arecoline (1.0, 3.0 and 10.0 mg/kg) generally recovered within 800 sec (Figure 1), which was consistent with previous reports on arecoline action times in behavioral demonstrations [8] and metabolic examinations [4]. Arecoline-induced decreases in BP may be due to arecoline-mediated relaxation of the aorta endothelium and/or improvement of vasorelaxation [2].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The BP changes induced by arecoline (1.0, 3.0 and 10.0 mg/kg) generally recovered within 800 sec (Figure 1), which was consistent with previous reports on arecoline action times in behavioral demonstrations [8] and metabolic examinations [4]. Arecoline-induced decreases in BP may be due to arecoline-mediated relaxation of the aorta endothelium and/or improvement of vasorelaxation [2].…”
Section: Discussionsupporting
confidence: 89%
“…Arecoline has long been known to exhibit multiple cholinomimetic effects that are predominantly parasympathetic in nature. Such effects have frequently been studied in animal models and observed in clinical settings, including effects on stress reduction, cardiovascular modulation, digestive promotion, and endocrine functions [5][6][7][8]20,21]. However, relatively little is known about how arecoline regulates BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies in Taiwan revealed dose-dependent increases in central and general obesity [ 148 ], and higher prevalence rates of metabolic syndrome [ 146 ] and type 2 diabetes [ 149 ] in areca nut chewers. Under conditions of starvation including under-nutrition, areca nut has toxic effects on the endocrine system leading to thyroid dysfunction and metabolic stress [ 150 ]. Experimentally, areca nut exposures induced glucose intolerance in adult mice, as well as in the F1 and F2 offspring of betel-fed parents [ 135 , 136 ], reflecting transgenerational transmission of disease.…”
Section: The Rising Tide Of Insulin Resistance Diseases and Cognimentioning
confidence: 99%
“…Arecoline is a natural cholinomimetic drug that evokes a wide spectrum of pharmacological effects on the nervous, cardiovascular, digestive, and endocrine systems, and also has anti-parasitic effects ( Peng W et al, 2015 ; Peng W et al, 2015 ; Liu et al, 2016 ). Arecoline exhibits multiple adverse effects, including growth retardation, developmental defects, locomotive impairment, cardiovascular disorders, and hyporeflexia, as shown in studies of zebrafishes, mice, rats, and humans ( Pichini et al, 2005 ; Peng W. H et al, 2015 ; Peng et al, 2016 ; Dasgupta et al, 2017 ; Dasgupta et al, 2018 ; Winger, 2021 ). Arecoline induces severe toxicity on cellular and molecular levels, such as oral submucosal fibrosis, oral squamous cell carcinoma, and genotoxicity ( Liu et al, 2016 ; Drake and Pjh, 2018 ).…”
Section: Introductionmentioning
confidence: 99%